Product under Summation (Part 3)

Calculus Level 5

S = 1 + 1 3 2 ( 1 2 ) + 1 5 2 ( 1 3 2 4 ) + 1 7 2 ( 1 3 5 2 4 6 ) + = 1 + r = 1 [ 1 ( 2 r + 1 ) 2 k = 1 r ( 2 k 1 2 k ) ] \begin{aligned} \text{S} &= 1 + \dfrac{1}{3^2}\left( \dfrac{1}{2}\right) +\dfrac{1}{5^2} \left( \dfrac{1\cdot 3}{2\cdot 4} \right) + \dfrac{1}{7^2}\left( \dfrac{1\cdot 3 \cdot 5}{2\cdot 4 \cdot 6} \right) + \ldots \\ & = 1 + \sum_{r=1}^{\infty} \left[ \dfrac{1}{(2r+1)^2}\prod_{k=1}^{r}\left(\dfrac{2k-1}{2k}\right) \right] \end{aligned}

S \text{S} can be expressed as

A π ln ( B ) C \dfrac{{\text{A} \pi}\ln (\text{B})}{\text{C}}

where A {\text{A}} , B {\text{B}} and C {\text{C}} are positive integers, A {\text{A}} and C {\text{C}} are coprime and B {\text{B}} is a prime number.

Evaluate A + B + C {\text{A}}+{\text{B}}+{\text{C}} .


See also : Part 1 , Part 2 , Part 4


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ishan Singh
Jan 27, 2016

Let f ( a ) = 1 1 + a + r = 1 [ 1 ( 2 r + a + 1 ) k = 1 r ( 2 k 1 2 k ) ] \displaystyle f(a) = \dfrac{1}{1+a} + \sum_{r=1}^{\infty} \left[ \dfrac{1}{(2r+a+1)}\prod_{k=1}^{r}\left(\dfrac{2k-1}{2k}\right) \right]

= 0 1 x a d x + r = 1 [ k = 1 r ( 2 k 1 2 k ) 0 1 x 2 r + a d x ] \displaystyle = \int_{0}^{1} x^{a} \mathrm{d}x + \sum_{r=1}^{\infty} \left[ \prod_{k=1}^{r}\left(\dfrac{2k-1}{2k}\right) \int_{0}^{1} x^{2r+a} \mathrm{d}x \right]

= 0 1 x a r = 1 [ x 2 r k = 1 r ( 2 k 1 2 k ) d x ] + 0 1 x a d x = \displaystyle \int_{0}^{1} x^{a} \sum_{r=1}^{\infty} \left[ x^{2r} \prod_{k=1}^{r}\left(\dfrac{2k-1}{2k}\right) \mathrm{d}x \right] + \int_{0}^{1} x^{a} \mathrm{d}x

Using infinite binomial series, we have,

f ( a ) = 0 1 x a ( 1 1 x 2 1 ) d x + 0 1 x a d x f(a) = \displaystyle \int_{0}^{1} x^a \left(\dfrac{1}{\sqrt{1-x^2}} - 1 \right) \mathrm{d}x + \int_{0}^{1} x^a \mathrm{d}x

= 0 1 x a 1 x 2 d x = \displaystyle \int_{0}^{1} \dfrac{x^a}{\sqrt{1-x^2}} \mathrm{d}x

Let x = sin θ x = \sin \theta

f ( a ) = 0 π 2 sin a θ d θ \displaystyle \implies f(a) = \int_{0}^{\frac{\pi}{2}} \sin^a \theta \ \mathrm{d}\theta

= 1 2 B ( p + 1 2 , 1 2 ) \displaystyle = \dfrac{1}{2} \operatorname{B} \left(\dfrac{p+1}{2}, \dfrac{1}{2}\right)

= 1 2 Γ ( a + 1 2 ) Γ ( 1 2 ) Γ ( a + 2 2 ) = \displaystyle \dfrac{1}{2} \dfrac{\Gamma \left(\dfrac{a+1}{2}\right) \Gamma \left(\dfrac{1}{2}\right)}{\Gamma\left(\dfrac{a+2}{2}\right)}

Using Gamma duplication formula, we have,

f ( a ) = π 2 a + 1 Γ ( a + 1 ) Γ 2 ( a + 2 2 ) ; a > 1 f(a) = \displaystyle \dfrac{\pi}{2^{a+1}} \dfrac{\Gamma (a+1)}{\Gamma^2\left(\dfrac{a+2}{2}\right)} \quad ; \quad a > -1

Required series is f ( 0 ) -f'(0) . Evaluating it, we have,

S = π ln 2 2 \text{S} = \boxed{\dfrac{\pi \ln 2}{2}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...